3D Vertically Aligned Li Metal Anodes with Ultrahigh Cycling Currents and Capacities of 10 mA cm−2/20 mAh cm−2 Realized by Selective Nucleation within Microchannel Walls. Issue 7 (17th January 2020) - Gao, Xuejie; Yang, Xiaofei; Adair, Keegan; Li, Xiaona; Liang, Jianwen; Sun, Qian; Zhao, Yang; Li, Ruing; Sham, Tsun‐Kong; Sun, Xueliang
Abstract: Although metallic lithium is regarded as the "Holy Grail" for next‐generation rechargeable batteries due to its high theoretical capacity and low overpotential, the uncontrollable Li dendrite growth, especially under high current densities and deep plating/striping, has inhibited its practical application. Herein, a 3D‐printed, vertically aligned Li anode (3DP‐VALi) is shown to efficiently guide Li deposition via a "nucleation within microchannel walls" process, enabling a high‐performance, dendrite‐free Li anode. Moreover, the microchannels within the microwalls are beneficial for promoting fast Li + diffusion, supplying large space for the accommodation of Li during the plating/stripping process. The high‐surface‐area 3D anode design enables high operating current densities and high areal capacities. As a result, the Li–Li symmetric cells using 3DP‐VALi demonstrate excellent electrochemical performances as high as 10 mA cm −2 /10 mAh cm −2 for 1500 h and 5 mA cm −2 /20 mAh cm −2 for 400 h, respectively. Additionally, the Li–S and Li–LiFePO4 cells using 3DP‐VALi anodes present excellent cycling stability up to 250 and 800 cycles at a rate of 1 C, respectively. It is believed that these new findings could open a new window for dendrite‐free metal anode design and pave the way toward energy storage devices with high energy/power density. Abstract : A 3D‐printed, vertically aligned Li anode (3DP‐VALi) is shown to efficiently guide Li deposition via a "nucleation within microchannel wall" process, supplying large space for the accommodation of Li during the plating/stripping process, and then enabling a high‐performance dendrite‐free Li anode. As a result, the Li–Li symmetric cells using 3DP‐VALi demonstrate excellent electrochemical performance as high as 10 mA cm −2 /10 mAh cm −2 for 1500 h.